What a (damn) boor! – on the expressive unit jeden (one) - Kosek, Iwona (Papers in Linguistics, 2020)
The main objective of the analysis is to preliminarily characterize the syntactic-functional features of the string jeden (‘one’) in occurrences to the one given in the title. In a broader perspective, the paper can be treated as a part of the studies on description of language units (in the sense of Andrzej Bogusławski) as the main building material of utterances. The analysis leads to the conclusion that the described unit does not belong to the objective level of language and it is used with nouns referring to people, taking a postposition relative to those nouns. The unit can not function as a rheme in a thematic-rhematic structure. (It is primarily a rhematic comment.) Jeden is an expressive unit and it determines the (negative) evaluation.